2021
DOI: 10.1021/acs.langmuir.1c02451
|View full text |Cite
|
Sign up to set email alerts
|

Local Cross-Coupling Activity of Azide-Hexa(ethylene glycol)-Terminated Self-Assembled Monolayers Investigated by Atomic Force Microscopy

Abstract: Azide-oligo(ethylene glycol)-terminated self-assembled monolayers (N 3 -OEG-SAMs) are promising interfacial structures for surface functionalization. Its many potential applications include chemical/bio-sensing and construction of surface models owing to its cross-coupling activity that originates from the azide group and oligo(ethylene glycol) (OEG) units for non-specific adsorption resistance. However, there are only a few studies and limited information, particularly on the molecular-scale structures and lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 66 publications
0
2
0
Order By: Relevance
“…It should be noted that an atomic force microscope (AFM), which uses force rather than tunneling current as a probe, has the potential to enable observation at the molecular scale even in environments and molecular systems that are difficult to measure with STM, but AFM technology with true atomic resolution is not commonly used and seems to be limited to specific research groups. Molecular resolution imaging of oligo EG-terminated SAMs formed on Au(111) surfaces in aqueous solution has been reported by Asakawa and Fukuma’s group using frequency modulation AFM. , They found that most of the EG chains in a hexa EG SAM are closely packed and well-ordered to present a molecularly flat surface, even in an aqueous solution.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…It should be noted that an atomic force microscope (AFM), which uses force rather than tunneling current as a probe, has the potential to enable observation at the molecular scale even in environments and molecular systems that are difficult to measure with STM, but AFM technology with true atomic resolution is not commonly used and seems to be limited to specific research groups. Molecular resolution imaging of oligo EG-terminated SAMs formed on Au(111) surfaces in aqueous solution has been reported by Asakawa and Fukuma’s group using frequency modulation AFM. , They found that most of the EG chains in a hexa EG SAM are closely packed and well-ordered to present a molecularly flat surface, even in an aqueous solution.…”
Section: Introductionmentioning
confidence: 96%
“…Molecular resolution imaging of oligo EG-terminated SAMs formed on Au(111) surfaces in aqueous solution has been reported by Asakawa and Fukuma's group using frequency modulation AFM. 19,20 They found that most of the EG chains in a hexa EG SAM are closely packed and well-ordered to present a molecularly flat surface, even in an aqueous solution.…”
Section: ■ Introductionmentioning
confidence: 99%